Prospective transGEICAM study of the impact of the 21-gene Recurrence Score assay and traditional clinicopathological factors on adjuvant clinical decision making in women with estrogen receptor-positive (ER1) node-negative breast cancer - Albanell, J.; González, A.; Ruiz-Borrego, M; Alba-Conejo, Emilio; García-Saenz, J.A.; Corominas, J. M.; Burgues, O.; Furio, V.; Rojo, A.; Palacios, J.; Bermejo, B.; Martínez-García, M.; et al. (Elsevier, 2012)
This study examined the impact of the Recurrence Score (RS) in Spanish breast cancer patients and explored the associations between clinicopathological markers and likelihood of change in treatment recommendations. Patients and methods: Enrollment was offered consecutively to eligible women with estrogen receptor-positive; human epidermal growth factor receptor 2-negative, node-negative breast cancer. Oncologists recorded treatment recommendation and confidence in it before and after knowing the patient’s RS. Results: Treatment recommendation changed in 32% of 107 patients enrolled: in 21% from chemohormonal (CHT) to hormonal therapy (HT) and in 11% from HT to CHT. RS was associated with the likelihood of change from HT to CHT (P < 0.001) and from CHT to HT (P < 0.001). Confidence of oncologists in treatment recommendations increased for 60% of cases. Higher tumor grade (P = 0.007) and a high proliferative index (Ki-67) (P = 0.023) were significantly associated with a greater chance of changing from HT to CHT, while positive progesterone receptor status (P = 0.002) with a greater probability of changing from CHT to HT. Conclusions: Results from the first prospective European study are consistent with published experience and use of the RS as proposed in European clinical practice guidelines and provide evidence on how Oncotype DX and clinicopathological factors are complementary and patient selection may be improved.
Este artículo ha sido publicado en Annals of Oncology. Esta versión tiene Licencia Creative Commons CC-BY.
Keywords: Mamas - Cáncer; Quimioterapia; Breast cancer; Chemotherapy; Estrogen receptor-positive; Oncotype DX; Recurrences Score; Receptor de estrógenos positivo; Riesgo de recurrencia; Recidiva